The Effectiveness of Internalizing Moral Values through Qur'anic Learning at Children's Boarding School - Yanto, Ferry; Meliana, Nia; Rosodor, Suraining; Saifullah, Ragil; Etikoh, Nuning (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the process of internalizing moral values in learning the Qur'an at the Nurul Ahmadi Children's Boarding School Catakgayam Mojowarno Jombang. Using a qualitative approach with a case study type, the research was conducted through participatory observation, in-depth interviews, and documentation studies. The results showed that the pesantren implemented a structured learning system with three learning times a day using the classical-individual method. The internalization of moral values is carried out through three stages: providing information, practice, and habituation, which is supported by the habituation method, setting rules with clear consequences, and providing motivation. This program is proven to be effective in shaping the character of santri, reflected in positive changes in discipline, language use, and adab towards teachers. The success of this program is supported by the commitment of the teachers in providing examples and the consistency of the implementation of the learning system. The internalization model of moral values applied makes a significant contribution to the development of pesantren-based character education, especially in early childhood students, and can be a reference for other Islamic educational institutions in developing similar programs.